Politics & gender. - American Political Science Association Women and Politics Research Section (Cambridge [England] New York, New York Cambridge University Press, 2005)
Publishes the scholarship on gender and politics and on women and politics. It aims to represent the full range of questions, issues, and approaches on gender and women across the major subfields of political science, including comparative politics, international relations, political theory, and U.S. politics
UP System perpetual contents: 2005-2021
Title from journal title screen (Cambridge Core, viewed September 14, 2023)
Keywords: Sex role -- Political aspects -- Periodicals; Women -- Political activity -- Periodicals